Punishment, education and reintegration policies in a penitentiary housing convicted youth in Turkey: a study in the Izmir juvenile education house - Kavur, Nilay. (Thesis (M.A.) - Bogazici University. Atatürk Institute for Modern Turkish History, 2012., 2012)
This thesis scrutinizes the interpenetration of the principles of punishment and education at the discursive and practical level through focusing on the Izmir Juvenile Education House which is one of the penitentiaries receiving convicted youth in Turkey. From the very beginning, penitentiaries for juvenile convicts have employed educatory practices, and particularly vocational training through industrial or service sector works. Today, the Juvenile Education House which receives the convicted youth in Turkey incorporates educational practices as the basis of its correction method in the form of formal and vocational training. The main concern of this study is to illuminate today’s Juvenile Education Houses’ governance of convicted youth as it is experienced and perceived by the convicted youth, itself. The historical transformation of the Juvenile Education House is also helpful in scrutinizing its institutional discourse. Today the specific educational levels of the convicted youth determine their programs in the Juvenile Education House, while the education received in relation to this background, within the walls of the institution, results in diverse and distinct experiences of conviction itself. In addition, techniques of discipline, surveillance, dominance, subjectification and, above all, self-formation stand out as the primary power mechanisms to shape the inmate as the convicts’ presence in the institution is determined minute by minute via daily schedules. Thus, the self-positioning of the Juvenile Education House, in relation to other correctional facilities, eventuates in distinct punitive policies and practices intrinsic to the institution itself. The analysis of these policies and practices is based on in-depth interviews and a focus group conducted with the residents as well as participant observation within the Đzmir Juvenile Education House.
Keywords: Juvenile delinquents -- Education -- İzmir -- Turkey.; Juvenile detention homes -- İzmir -- Turkey.